The Life Span Model of Suicide and Its Neurobiological Foundation - Ludwig, Birgit; Roy, Bhaskar; Wang, Qingzhong; Birur, Badari; Dwivedi, Yogesh (Frontiers in Neuroscience, 2017)
The very incomprehensibility of the suicidal act, has been occupying the minds of researchers and health professionals for a long time. Several theories of suicide have been proposed since the beginning of the past century and a myriad of neurobiological studies have been conducted over the past two decades in order to elucidate its pathophysiology. Both neurobiology and psychological theories tend to work in parallel lines that need behavioral and empirical data respectively, to confirm their hypotheses. In this review, we are proposing a “Life Span Model of Suicide” with an attempt to integrate the “Stress-Diathesis Model” and the “Interpersonal Model of Suicide” into a neurobiological narrative and support it by providing a thorough compilation of related genetic, epigenetic, and gene expression findings. This proposed model comprises three layers, forming the capability of suicide: genetic factors as the predisposing Diathesis on one side and Stress, characterized by epigenetic marks on the other side, in between gene expression and gene function which are thought to be influenced by Diathesis and Stress components. The empirical evidence of this model is yet to be confirmed and further research, specifically epigenetic studies in particular are needed to support the presence of a life-long, evolving capability of suicide, and identify its neurobiological correlates.